Dental and oral health education in parents of taam avicenna playgroup students - Agni Febrina Pargaputri; Aulia Dwi Maharani; Fauziah Julike Patrika (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Oral and dental health education aims to increase knowledge that leads to better dental and oral health behaviors. Parents play an important role in children's behavior to maintain dental and oral health. Lack of behavior to maintain healthy teeth can be caused by low knowledge of dental and oral health. This activity aim to provide dental and oral health education to parents of students in Taam Avicenna Surabaya playgroup. This activity was carried out by providing dental health education media such as flipcharts, posters, and dental phantoms. Then post-test was given to the participants. Questionnaires regarding the behavior of maintaining dental and oral health were also given. The results showed that the understanding of parents with good categories was more than those with moderate and low categories. This means that some parents can receive dental health education well. Providing dental health education has a positive impact on understanding and knowledge of dental and oral health in parents. It can be concluded that by giving dental health education for parents of students in Taam Avicenna Surabaya playgroup, could enhance understanding and knowledge of dental and oral health so that it could help parents to improve behavior in oral and dental health.